Pengembangan media pembelajaran membaca aksara Jawa berbasis video edutainment pada peserta didik kelas V sekolah dasar - Asti Nafsiah; Retno Winarni; Joko Daryanto (Universitas Sebelas Maret, 2022)
The purpose of this study is to describe the development of learning media for reading Javanese scripts based on edutainment video for fifth-grade students of Mijen Public Elementary School, Surakarta. This type of research is research and development. The development based on the Borg and Gall development research procedure which has been simplified by the Puslitjaknov Team. The subject were fifth-grade students at Mijen Public Elementary School, Surakarta. Sources of data come from students and teacher. Data collection techniques using interviews and document analysis. Validation techniques are carried out by material expert, media expert, and practitioner expert. The making of learning media using Adobe Premiere Pro, Adobe After Effects, and Adobe Photoshop. The results showed that the development was declared very feasible. The feasibility level of this learning media based on the assessment of: 1) material expert obtained a total score of 70 with an average 3.5; 2) media expert obtained a total score of 69 with an average 3.45; 3) practitioner expert obtained a total score of 155 with an average 3.875.